Post‐Migration Stress: Racial Microaggressions and Everyday Discrimination - Quassoli, Fabio (2023)
In 1991, Philomena Essed highlighted the importance of studying contemporary racism, focusing on the interplay between the macro‐social dimension and its constant reactivation in everyday interactions. Later, psychologists redefined the pervasive experience of racism in everyday encounters in terms of racial microaggressions. Migrants and asylum seekers today constitute “ideal” candidates for this kind of experience. This is due to the persistent historical processes that harken back to Western colonialism and imperialism, as well as the growing hostility towards people migrating from the Global South. This hostility has been brewing for several decades in Western countries, and it manifests in both everyday informal interactions and institutional contexts, where migrants and asylum seekers constantly face racist attitudes.